Inferring Firn Permeability from Pneumatic Testing: A Case Study on the Greenland Ice Sheet - Sommers, Aleah N.; Rajaram, Harihar; Weber, Eliezer P.; MacFerrin, Michael J.; Colgan, William T.; Stevens, C. Max (Frontiers in Earth Science, 2017)
Across the accumulation zone of the Greenland ice sheet, summer temperatures can be sufficiently warm to cause widespread melting, as was the case in July 2012 when the entire ice sheet experienced a brief episode of enhanced surface ablation. The resulting meltwater percolates into the firn and refreezes, to create ice lenses and layers within the firn column. This is an important process to consider when estimating the surface mass balance of the ice sheet. The rate of meltwater percolation depends on the permeability of the firn, a property that is not well constrained in the presence of refrozen ice layers and lenses. We present a novel, inexpensive method for measuring in-situ firn permeability using pneumatic testing, a well-established technique used in environmental engineering and hydrology. To illustrate the capabilities of this method, we estimate both horizontal and vertical permeability from pilot tests at six sites on the Greenland ice sheet: KAN-U, DYE-2, EKT, NASA-SE, Saddle, and EastGRIP. These sites cover a range of conditions from mostly dry firn (EastGRIP), to firn with several ice layers and lenses from refrozen meltwater (Saddle, NASA-SE, EKT), to firn with extensive ice layers (DYE-2 and KAN-U). The estimated permeability in firn without refrozen ice layers at EastGRIP agrees well with the range previously reported using an air permeameter to measure permeability through firn core samples at Summit, Greenland. At sites with ice lenses or layers, we find high degrees of anisotropy, with vertical permeability much lower than horizontal permeability. Pneumatic testing is a promising and low-cost technique for measuring firn permeability, particularly as meltwater production increases in the accumulation zone and ice layers and lenses from refrozen melt layers become more prevalent. In these initial proof-of-concept tests, the estimated permeabilities represent effective permeability at the meter scale. With appropriately higher vacuum pressures and more detailed monitoring, effective permeabilities over a larger scale may be quantified reliably, and multiple measurements during a season and across multiple years could improve understanding of the evolving firn structure and permeability. The technique is also suitable for broad application in Antarctica and other glaciers and ice caps.